Upaya Meningkatkan Motivasi dan Prestasi Belajar dengan Menggunakan Metode Diskusi pada Materi Iman Kepada Malaikat Di Kelas VII-I SMP Negeri 2 Pare Kabupaten Kediri - Ida Mahmudah (Jurnal Simki Postgraduate, 2022)
Based on initial observations in class VII-I of SMP Negeri 2 Pare, information was obtained that the learning outcomes of most students in the subject of Islamic Religious Education were still relatively low. The learning process for Islamic Religious Education at SMP Negeri 2 Pare often uses the lecture method. This has an impact on student learning outcomes which show that there are still many student test scores that do not meet the Minimum Completeness Criteria (KKM) set at SMP Negeri 2 Pare. Therefore, in this study the Discussion method was applied to improve student learning outcomes in class VII-I and to find out student responses to discussion learning on Faith in Angels material. This study aims to describe Islamic Religious Education with the application of the discussion method which can increase the motivation and learning achievement of Islamic Religious Education students on the material Faith in Angels. This study used a Class Action Design (PTK) which consisted of two cycles. Research data collection was carried out from October to December 2018. This research was in the form of student learning activities and achievements obtained through tests at the end of each cycle. Based on the results of research data analysis and discussion, it can be concluded as follows: 1) The Discussion Method can increase learning motivation in the material Faith in Angels by 16% from 70% in cycle 1 and 86% in cycle 2. 2) The Discussion Method can improve learning achievement in material Faith in Angels as indicated by an increase in the percentage of classical completeness by 23% from 77% in cycle 1 to 90% in cycle 2.